Spin superfluidity in the anisotropic XY model in the triangular lattice. (July 2016) - Lima, L.S.
Abstract: We use the SU(3) Schwinger׳s boson theory to study the spin transport properties in the two-dimensional anisotropic frustrated Heisenberg model in the triangular lattice at T =0. We have investigated the behavior of the spin conductivity for this model which presents an single-ion anisotropy. We study the spin transport in the Bose-Einstein condensation regime where we have that the t z bosons are condensed and the following condition is valid: 〈 t z 〉 = 〈 t z † 〉 = t . Our results show a metallic spin transport for ω > 0 and a superfluid spin transport in the limit of DC conductivity, ω → 0, where σ ( ω ) tends to infinity in this limit of ω . Abstract : Highlights: We employ SU(3) Schwinger boson formalism together with the Kubo formula to calculate the spin conductivity. We find the behavior of AC conductivity σ reg ( ω ) where the region Δ ω where the AC conductivity tends to infinity when ω → 0 . We determine the behavior of the spin transport properties at T =0.